Questions Opened by Post-humanism and Personal Originality - Barraca Mairal, Javier (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This text seeks to identify and group some of the most relevant questions posed by current transhumanism and its post-humanist drift. It reflects on its factual, ethical, legal, anthropological, and ontological questions. Its reductionisms are critically analyzed. The phenomenon is contrasted with the philosophical keys of originality, uniqueness, dignity, and creativity.